Contrasting Effects of Thrombin and the Thrombin Receptor Peptide, SFLLRN, on Aggregation and Release of 14C-Serotonin by Human Platelets Pretreated with Chymotrypsin or Serratia marcescens Protease - Kinlough-Rathbone, Raelene L; Perry, Dennis W; Packham, Marian A (Thrombosis and Haemostasis, 1995)
Chymotrypsin cleaves glycoprotein Ib (GPIb) on platelets and reduces their responsiveness to thrombin; platelets from patients with the Bernard-Soulier syndrome, which lack GPIb, are also less responsive to thrombin than platelets from normal donors. However, Bernard-Soulier platelets respond normally to the thrombin receptor peptide SFLLRN (13). We compared responses of14C-serotonin-labeled, chymotrypsin-treated platelets (and control platelets) to thrombin (0.25-2 U/ml) and SFLLRN (5–40 μM). Chymotrypsin treatment strongly inhibited thrombin-induced aggregation and release of14C-serotonin when concentrations of thrombin of 0.5 U/ml or lower were used, even though these responses of control platelets remained near the maximum. In contrast, there was little difference between the responses of control and chymotrypsin-treated platelets to SFLLRN, even when the responses of control platelets were less than maximal. Thus, chymotrypsin treatment greatly inhibits the response to thrombin of the seven transmembrane domain thrombin receptor cloned by Coughlin’s group (1, 2). Since Serratia marcescens protease also hydrolyses GPIb, but has less effect than chymotrypsin on other glycoproteins, we pretreated platelets with several concentrations of S. marcescens protease. Concentrations that abolished aggregation and release of14C-serotonin in response to thrombin had little effect on these responses to SFLLRN. One interpretation of these findings would be that by cleaving GPIb, both proteases are affecting an interaction that may be important for activation of the cloned receptor by thrombin, but irrelevant to activation of this receptor by SFLLRN. Alternatively, it may be that in addition to cleaving GPIb, both chymotrypsin and S. marcescens protease also cleave the cloned receptor at a site that results in the loss of SFLLRN, but do not affect the site on this receptor with which SFLLRN interacts.